Training on making decorative candles from used cooking oil for unproductive community groups in Penjaringan Village, North Jakarta - Rosmalia Dita Nugraheni; Dewi Syavitri; Puri Wijayanti; Nadhia Noor Syarifa; Ratih Yuni Astuti (Community Empowerment, 2022)
Used cooking oil has the potential to be recycled into decorative candles. However, the people who live in RT 12/RW 12 Kelurahan Penjaringan Utara, North Jakarta, particularly housewives, do not yet know how to use used cooking oil as a way to improve the family's finances. The purpose of this community service is to provide counseling and education about used cooking oil, including information on its health risks and how to recycle it into decorative candles. The community service approach entails preparation, counseling, and training in how to make decorative candles. The majority of participants used cooking oil more than 15 times in a month and 1-3 times the same cooking oil, according to the program's results. Additionally, there has been a shift in behavior regarding the color-based feasibility limit for used cooking oil, a decline in the number of people who throw used cooking oil down the drain, and increased motivation to recycle used cooking oil into decorative candles that can be sold. From the outcomes of this program, it can be inferred that the residents responded favorably to training on how to make decorative candles from used cooking oil.